Personal Mastery: Build Your Leadership Character to be a Great Leader - Arsy, Luna; Eidelweis, Akyaila; Saragih, Anggita Putri Soraya; Rusalam, Grevilla Deva Salsabela; Anggraini, Maulida Zahrah; Nasrullah, Mohammad Naufal; Dania, Ullaya Nazla; Romadlona, Nohan Arum (Inovasi Lokal, 2024)
Cultivating leadership skills from an early age is important. This is related to how they will lead in the future. The spirit of leadership in children is seen in the attitude shown, such as courage by children to face various situations and conditions that occur directly. Through this, knowledge about Personal Mastery is needed. Personal mastery is a factor of the human individual, where there is a continuous process for individuals to deepen personal vision, focus on their own strengths, develop self-patience and see reality objectively. In accordance with this statement, this article aims to provide information about Personal Mastery to provide an understanding of the importance of personal leadership development for each individual and help students connect the concept of personal leadership with their future educational and career goals. To achieve these goals, this service method is carried out using the lecture method with the help of PowerPoint media to display the material. The results of this article are the implementation of material counseling using the lecture method for students of class 8B Maarif Batu Junior High School is very useful in increasing knowledge about Personal Mastery. Lecture is essentially the process of transferring information from the teacher to the learning target. In the process of transferring information there are three important elements, namely the teacher, the material and the learning target. The lecture method is effectively used to increase one's knowledge.